Politicizing What's News: How Partisan Media Bias Occurs in News Production. Issue 3 (4th May 2021) - Shultziner, Doron; Stukalin, Yelena
ABSTRACT: Notions of partisan media bias and ideological influences on the news have become much more prevalent since Gans wrote Deciding What's News . We propose a framework to explain what partisan media bias is and how it operates. We argue that partisan bias occurs in two ways. First, editorial decisions influence the share of positive, neutral and negative content types, i.e., description bias. Second, partisan bias happens through production tools that emphasize or deemphasize the content of articles keeping it aligned with an outlet's news ideology. We conducted our study on the historic 2011 Occupy protest movement in Israel using 1837 news items from the six largest newspapers. We found that reporting was slanted to align with outlets' news ideology and that several production mechanisms were involved. Specifically, we found that front-page headlines, the sizing of articles, accompanying visuals, and protestors' perspectives were consistently and strategically employed. Our study concludes by considering its implications for researching partisan media bias and protest coverage.